A Multilevel Analysis of Determinants of Financial Aid for College Students - Yang, Po (Journal of Educational Studies, 2009)
Chinese financial aid system is a response to the reduced affordability of higher education and a way to improve the access of the disadvantaged groups to higher education.Based on a survey of 16,058 college students from 54 institutions in Beijing,this study made an empirical analysis of the influential factors of the financial aid for college students.The result indicates that the students from key universities receive more aid than students from other universities and the enrolment in key universities increases the probability of getting aid.In addition,female students,students with better educated fathers or from poor households,and CCP members receive more aid.Students with higher marks in college entrance examination,senior students and students in science related majors obtain significantly more aid.These findings provide empirical evidence for adjusting college financial aid policy in China.
Keywords: financial aid; multilevel analysis